'I was scared I will end up in another abortion': a mixed-methods study assessing the impact of COVID-19 pandemic and lockdown on the antenatal care of pregnant women in Puducherry, South India. (25th June 2021) - Ulaganeethi, Revathi; Dorairajan, Gowri; Ramaswamy, Gomathi; Thekkur, Pruthu; Olickal, Jeby Jose; Rajkumari, Nonika; Kumar Saya, Ganesh
Abstract: Background: As a mitigation measure for COVID-19 pandemic, lockdown was implemented in India for a period of 2 months (24 March–31 May 2020). Disruption in antenatal care (ANC) provisions during lockdown is expected due to diversion of public health facilities on pandemic. Objective: To assess the proportion of pregnant women who had not completed the ideal number of antenatal visits, availability of iron–folic acid (IFA) supplements and challenges in availing health services during the period of lockdown. Methods: A concurrent mixed-methods study was conducted among pregnant women in Puducherry, India. Information on obstetric characteristics and details regarding antenatal visits were collected through telephonic interviews. In-depth interviews were conducted to understand the perceived challenges in availing health services during the lockdown period. Results: Out of 150 pregnant women, 62 [41.3%; 95% confidence interval (CI) 33.6–49.3] did not complete the ideal number of visits and 61 (40.7%, 95% CI 32.7–49.0) developed health problems. Out of 44 women who received medical care for health problems, 11 (25%) used teleconsultation. Of all the women, 13 (8.7%, 95% CI 4.9–14.0) had not taken the IFA supplements as prescribed by the health provider. Economic hardship, restricted mobility, lack of information about the health system changes and psychological stress due to the fear of COVID were the challenges in accessing care. Conclusions: Two out of five pregnant women did not complete the ideal number of visits and developed health problems during the lockdown period.